Subluxation of the Palmar Radioulnar Ligament As a Cause of Blocked Forearm Supination: A Case of DRUJ Locking - Takahashi, Yuichiro; Nakamura, Toshiyasu; Sato, Kazuki; Toyama, Yoshiaki (Journal of Wrist Surgery, 2013)
We report a case of locking of the distal radioulnar joint (DRUJ) due to interposition of a flap of the palmar radioulnar ligament (RUL) torn from the triangular fibrocartilage complex (TFCC). We released the blockage by elevating the flap and partially resecting a portion of the triangular fibrocartilage (TFC) arthroscopically.
Keywords: locking; distal radioulnar joint; triangular fibrocartilage complex; pronation contracture; radioulnar ligament